Morphometric study of proximal femur in fractured and non-fractured post menopausal women - Nayak, Lopamudra; Senapati, Susmita; Panda, Sitanshu Kumar; Chinara, Prafulla Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was conducted to investigate the risk of hip fracture using proximal femoral morphometry in fractured and nonfractured postmenopausal women. Methods: We conducted an observational cross-sectional study with 138 postmenopausal women (49 fractured and 89 nonfractured). The hip axis length (HAL), femoral neck axis length (FNAL), acetabular width (AW), femoral head width (FHW), femoral shaft width (FSW), and femoral neck shaft angle (FNSA) were measured in all cases by dual energy X-ray absorptiometry. We also studied the correlation between body mass index (BMI) with all the parameters in fractured and control groups. Results:The mean age, height, weight, and BMI were 61.24±3.23, 163.94±7.84 cm, 71.88±9.14 kg, and 26.72±2.78 kg/m², respectively, in fractured patients. In nonfractured patients the values were 59.73±5.32, 161.73±4.25 cm, 69.54±6.25 kg, and 26.74±2.23 kg/m² respectively. The mean HAL, FNAL, AW, FHW, FSW, and FNSA were 130.5±3.18 mm, 111.26±3.64 mm, 18.2±1.91 mm, 53.46±1.51 mm, 37.45±1.82 mm, and 132.76±3.15 degree in case group and 130.84±4.74 mm, 112.48±4.08 mm, 17.57±2.32 mm, 53.4±1.86 mm, 35.29±1.82 mm, and 128.76±3.6° in control group, respectively. Conclusion: The femoral parameters such as HAL, FNAL, AW, and FHW do not indicate any correlation between fractured and control groups, whereas FSW and FNSA were significantly higher in case group. The FNSA was having significant negative correlation with BMI in fractured group while that was having a significant positive correlation in the nonfractured group. This observation will be helpful in exploration of its clinical significance in proximal femoral fracture. Keywords: Proximal femur, Morphometry, Postmenopausal, Fracture.